Assessment of Badakhshan climatic condition for production and marketing of saffron - Wafa, Abdul Sami (International Journal of Innovative Research and Scientific Studies, 2021)
A research was conducted in 2019 to assess the favorability of Badakhshan climatic condition for production and marketing of saffron. The data was collected through questionnaires from 30 participants of Badakhshan saffron farmers, specialists, professors, school of economics and agriculture departments. According to the average results of the total respondents it is said that climatic condition of Badakhshan is 76.2% favorable for saffron cultivation. The marketing evaluation is said that 23% of Badakhshan saffron is consumed at home, 40% is sold in local market, 20% percent is sold in national market and 17% is sold in international markets. 36% respondents believe that saffron has very little effect, and 57% said that it has little impact and 7% of the respondent answered that saffron has great effects on the farmers’ income in Badakhshan. Therefore, it is concluded that the Badakhshan climatic condition is favorable for production and marketing of saffron but it requires government and relevant agriculture departments and NGO’s to supply saffron roots, focus on farmers training and marketing of saffron to raise its quality level and increase the farmer’s income in Badakhshan.